2017
DOI: 10.2486/indhealth.2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of participatory training for the promotion of work-related health and safety among Korean farmers

Abstract: This study was conducted to explore the effectiveness of participatory training for promoting farmer’s health and reducing agricultural work-related injuries. Candidates for this study included 595 farmers in 8 rural villages of South Korea. The one-day course participatory training was administered to 217 (36.5%) farmers and included an action-checklist, a good example presentation, and group discussion. The follow-up visit to participants’ houses and farms was performed after 1 to 3 months. A direct intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The compliance with the action plan showed continuance, with compliance rates of 61.4%, 57.6%, and 53.2% within 6 months after the WBSM program in first, second, and third year, respectively. This coincided with previous studies demonstrating that compliance with an action plan was maintained for periods of 3 and 6 months after an intervention [ 18 , 21 , 25 ]. It was obvious that the MetS action checklist played an important role for traditional retail market workers to create plans by themselves and promoted successful improvement outcomes in managing metabolic risk factors and lifestyle habits [ 12 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The compliance with the action plan showed continuance, with compliance rates of 61.4%, 57.6%, and 53.2% within 6 months after the WBSM program in first, second, and third year, respectively. This coincided with previous studies demonstrating that compliance with an action plan was maintained for periods of 3 and 6 months after an intervention [ 18 , 21 , 25 ]. It was obvious that the MetS action checklist played an important role for traditional retail market workers to create plans by themselves and promoted successful improvement outcomes in managing metabolic risk factors and lifestyle habits [ 12 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Participants were asked to use the MetS action checklist to identify actions for improvement and propose practical health improvements applicable in a range of specific traditional retail market worksites [ 15 ]. Counseling was delivered to help participants recognize solutions through self-reliance and plan practical actions [ 25 ]. At the end of the third month and the sixth month, respectively, counselors supported and evaluated implemented improvement actions [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on these findings, it is suggested to examine the characteristics of the facilitators’ outcomes in the use of participatory approaches. Among the previous studies concerning the roles of the facilitators, several studies have already reported the situations in which workplace safety and health issues were resolved as results of the improvements . However, few studies have focused on the underlying aspects such as outcomes resulting from the use of a participatory approach .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the approach was identified as an effective and practical method for promoting comprehensive risk management involving both workers and employers . However, many articles about the outcomes of workplace environment improvement considered only the results of improvements, such as whether a safer and healthier work environment was achieved or OSH issues were addressed in participatory programs . In contrast, as seen in the Community‐Based Participatory Research (CBPR), findings in effective methods for solving community's health issues have been accumulated and the multifaceted evaluation systems are developed .…”
Section: Introductionmentioning
confidence: 99%
“…Workers' risk awareness is the first step in ensuring workplace safety and health [4]. Hence, risk perception and active worker participation in the planning, execution, and evaluation of actual intervention techniques are of great importance [5,6].…”
Section: Introductionmentioning
confidence: 99%